Erratum: Molecular basis of cooperativity in pH-triggered supramolecular self-assembly - Yang Li (Nature Portfolio, 2016)
Nature Communications 7: Article number: 13214 (2016); Published: 27 October 2016; Updated: 16 December 2016 Figure 5 of this article contained errors introduced during the production process. In Fig. 5c, the minimum value of the x axis (left hand side) should be −1.0 and not 1.0. Additionally, the maximum value of the y axis in Fig.